A Multi-Platform GUI for Circuit Schematic Design Using CircuiTikZ - Pfannenmüller, Christof; Wiedemann, Jan Philipp Wiedemann; Kirzinger, Manuel; Weigel, Robert (Latin America Microwave Conference, 2025)
The powerful CircuiTikZ-package provides typesetting of electrical and electronic networks and is commonly used in all areas of electrical engineering. The TikZ-based syntax is powerful, but unintuitive and tedious, leading to a lot of time used for creating the schematic drawings. A browser-based graphical user interface (GUI) is presented that provides features such as "what you see is what you get" (WYSIWYG). The presented browser application lets the user design the circuitry graphically. The tool calculates the component positions based on user input and exports (Circui)TikZ code for use in Latex like typesetting documents significantly speeding up the circuit schematic drawing proces

A Novel Integrated Power Detection Circuit for Low Noise Amplifiers in Cellular Applications - Spielberger, Alexander; Scheller, Kai; Engelmann, Andre; Franchi, Norman; Weigel, Robert; Pfannenmüller, Christof (IEEE Wireless and Microwave Technology Conference (WAMICON) 2025, 2025)
A novel power sensing method, integrated in low noise amplifier architectures is presented and demonstrated in 130 nm SiGe BiCMOS technology. The power sensor architecture can be utilized to detect blocking signals by supply current varia- tions caused from different amplifier saturation states. Therefore the combined amplifier/power sensor architecture overcomes the need of additional components in the RF signal path for input power sensing. Two sensor architectures are compared while one is implemented. The architectures ability to indicate input power by amplifier saturation is proven by measurement. It is shown that the sensor gives direct feedback at early stages before the amplifier is in full saturation. The amplifier achieves a maximum gain of 14.31 dB and is optimized for the 5G low-band frequency range from 600 MHz to 1 GH
Keywords: Low-noise amplifier; integrated power sensor; mobile communication; Cellular technology; 5G; 4G

A Novel Neuropredictive SAR ADC Architecture for Ultra-Low Power Applications - Spielberger, Alexander; Pfannenmüller, Christof; Spitzkopf, Lucas; Armbrecht, Wolfgang; Schrotz, Albert-Marcel; Weigel, Robert; Franchi, Norman (68th IEEE International Midwest Symposium on Circuits and Systems, 2025)
This paper proposes a new type of neuromophic analog to digital converter, the neuropredictive SAR ADC. By estimation of the next input value using a neuromorphic predictor, the conversion time of a modified SAR ADC and thus the energy consumption of the ADC can be reduced. A demonstrator designed for audio signals shows an energy saving of 41.09% compared to conventional SAR sampling. This ADC architecture is an alternative for ultra-low power application
https://cris.fau.de/converis/publicweb/Publication/342443079
Keywords: neuromorphic adc; neuropredictive SAR; SAR; ultra-low power

Dynamic Antenna Impedance Tuning for Sub-GHz Systems - Dorn, Christian; Pfannenmüller, Christof; Gabsteiger, Jasmin; Kurin, Thomas; Lurz, Fabian; Hagelauer, Amelie (2025 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2025, 2025)
In all wireless systems, high power transfer from the RF front-end (RFFE) to the antenna is required. To achieve this, impedance matching between the RFFE and the antenna is necessary. Most applications assume a static antenna impedance for a given frequency band and thus only require a single static matching network per band. In reality, changing near-field conditions (e.g. due to human interaction) require a rapid adaption or in-band mismatch requires a finer change in impedance matching. This work introduces and compares several topologies that allow dynamic adaptive antenna impedance tuning in sub-GHz applications. They even permit a strong mismatch with a voltage standing wave ratio (VSWR) of 20:1 with a high power rating suitable for transmission in mobile applications.
CRIS-Team Scopus Importer:2025-04-04
Keywords: antenna; impedance; tuning

Performance Evaluation of a New Universal Time Domain Gating Algorithm - Zohner, Alina; Irnstorfer, Florian; Weigel, Robert; Pfannenmüller, Christof (2024 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2024)
This paper presents a new Time Domain Gating (TDG) algorithm to de-embed a Device Under Test (DUT). The algorithm uses scattering parameters (S-parameters) from a typical Vector Network Analyzer (VNA) as input data. The approach isolates the signal part belonging to the component under test from interfering elements, thus enabling stand-alone evaluation. Comparing the results with state-of-the-art commercial and open-source approaches validates the algorithm's performance and confirms its superiority in terms of user flexibility and accuracy. It allows continuous measurement and simultaneous de-embedding of a DUT. Furthermore, it features an optional compensation technique that removes unwanted gating effects and can be applied to any gate. Regardless of the manufacturer, the algorithm can be combined with any VNA. Since it was implemented independently of the measurement equipment, it is universally applicable, for example, to locally remote test objects. The comparison with current implementations shows minimal errors for the proposed algorithm. In addition, several ambiguities in commercially available state-of-the-art algorithms can be identified.<br
Keywords: Performance evaluation; Accuracy; Current measurement; Network analyzers; Logic gates; Vectors; Scattering parameters; time domain gating; de-embedding; VNA; S-parameters; open-source; time gating; TDG

Resistive Matching Techniques in Electrical Balanced Duplexer Systems - Spielberger, Alexander; Pfannenmüller, Christof; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference 2024, 2024)
Electrical Tunable Duplexers allow multi-use of RF front ends. A broadband impedance tuner is required for high isolation. This paper deals with how the use of a Digital Tunable Resistor (DTR) can improve the tuning range of such a tuner. In the following a possible DTR realization is shown, which converts a linear control voltage into a linear relation of the reflection coefficient. This can be used to map a reflection coefficient of -0.9 to 1 up to a frequency of 6 GHz. <br
Keywords: electrical balanced duplexer; mobile communication; resistive matching; digital tunable resistor